(untitled) (Research, Society and Development, 2022)
The expansion of cities has altered urban mobility, which has become a challenge for policy makers. At the same time, technological developments and access to mobile applications have also grown, since they provide information in order to facilitate urban displacement. Thus, the eradication of obstacles aimed at e-inclusion contributions to the exercise of citizenship and social equity. The objective of the work is to investigate what are the determinants of e-inclusion and digital inequality to discriminate users and non-users of urban mobility applications. A mixed approach was carried out using a meta-analytical approach, associated with the discriminating statistical technique and hypothesis testing of the data collected through an electronic questionnaire applied to 205 respondents in Brazil. The results found showed four discriminating variables of users and non-users of urban mobility applications, namely: income, age, difficulty in using digital technology and learning to use digital technology. Among these, only the income variable showed significance in the hypothesis tests. The research reveals that income is an important variable in the process of e-inclusion and digital inequality and should be considered by the public managers.